2015
DOI: 10.1107/s2053230x15012698
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RizA, anL-amino-acid ligase fromBacillus subtilis

Abstract: RizA is an l-amino-acid ligase from Bacillus subtilis that participates in the biosynthesis of rhizocticin, an oligopeptide antibiotic. The substrate-free form of RizA has been crystallized and the structure was solved at 2.8 Å resolution. The amino-acid-binding site appears to be capable of accommodating multiple amino acids, consistent with previous biochemical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…5A; see also Fig. S11A to C in the supplemental material) based on that of RizA (PDB 4WD3), a well-defined ligase in the rhizociticin pathway from Bacillus subtilis (20). According to this model, PolG contains three independent domains (designated A, B, and C domains) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5A; see also Fig. S11A to C in the supplemental material) based on that of RizA (PDB 4WD3), a well-defined ligase in the rhizociticin pathway from Bacillus subtilis (20). According to this model, PolG contains three independent domains (designated A, B, and C domains) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to this model, PolG contains three independent domains (designated A, B, and C domains) ( Fig. 5A), which are conserved in the L-amino acid ligases, including RizA, BL0025, and BacD (20). Furthermore, in silico analysis showed that the five conserved residues deduced for ATP binding in RizA could also be discerned in PolG (Lys110, Lys150, Glu267, Glu188, and Glu280) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LALs contain the ATP-grasp fold, which is composed of three conserved domains referred to as the A-domain (N-terminal domain), the B-domain (central domain) and the C-domain (Cterminal domain). These three domains commonly grasp the ATP molecule, and also provide binding sites for the Mg2 + ion and the amino-acid substrate [54].…”
Section: Discussionmentioning
confidence: 99%
“…LALs contain the ATP-grasp fold, which is composed of three conserved domains referred to as the A-domain (N-terminal domain), the B-domain (central domain) and the Cdomain (C-terminal domain). These three domains commonly grasp the ATP molecule, and also provide binding sites for the Mg2+ ion and the amino-acid substrate [54].…”
Section: Discussionmentioning
confidence: 99%